Nurses' first aid attitude toward second-degree burns patients at Martha Friska General Hospital, Pulo Brayan - Tani Astuti; Erika (Science Midwifery, 2023)
World Health Organization (WHO) stated in 2014 that burns had become a global and crucial problem in developing countries. Burns are damage, whether directly or indirectly, to skin tissue that does not rule out the possibility of reaching internal organs caused by direct contact with heat sources, namely fire, steam, chemicals, radiation, electric current, and frigid temperatures. This descriptive research was conducted at Martha Friska Pulo Brayan Hospital, with a population of all nurses serving in the Emergency Room of Martha Friska Pulo Brayan General Hospital as many as 18 respondents. This study used a total sampling technique, where sampled the entire population, namely 18 respondents in the ER room at Martha Friska Pulo Brayan General Hospital. The results obtained from nurses' attitude in first aid for patients with second-degree burns at Martha Friska Pulo Brayan General Hospital based on the noble knowledge of as many as ten respondents (55.5%), the minority with sufficient knowledge of as many as eight respondents (44.4%), behavior based on the attitude of the majority of positive respondents as many as 16 respondents (88.8%), the minority of negative respondents as many as two respondents (11.1%), behavior based on actions taken by 11 respondents (61.1%), minority actions carried out by six respondents (38.8%). Based on the results, the researchers saw that almost all nurses in the ER had run well about burns. The results based on the research are expected for nurses to improve the quality of higher-quality services further and further improve knowledge, attitudes, and actions in health services.